Pre-Stroke Depression in Ghana and Nigeria: Prevalence, Predictors and Association With Poststroke Depression. (January 2022) - Ojagbemi, Akin; Akinyemi, Joshua; Wahab, Kolawole; Owolabi, Lukman; Arulogun, Oyedunni; Akpalu, Josephine; Akpalu, Albert; Ogbole, Godwin; Akinsanya, Cynthia; Wasiu, Adeniyi; Tito-Ilori, Moyinoluwa; Adekunle, Fakunle; et al.
Objectives: Depression is a risk factor for stroke. There is a knowledge gap on the predictors of prestroke depression in stroke survivors living in low- and middle-income countries (LMICs). We estimated prevalence and predictors of prestroke depression, as well as its association with poststroke depression (PSD) in the largest study of stroke in Africa. Methods: We evaluated information collected as part of the Stroke Investigative Research and Education Network (SIREN) study, a multicentre, case-control study conducted at 15 sites in Ghana and Nigeria. Prestroke depression status was ascertained in stroke survivors using a validated self-report tool, while PSD was assessed using a stroke specific screening tool for depression ("HRQOLISP-E"). Independent associations were investigated using complementary log-log regression and binary logit models. Results: Among 1, 977 participants, prestroke depression was found in 141 (7.1%). In multivariate analyses, prestroke depression was significantly associated with tachycardia (OR = 2.22, 95% CI = 1.37-3.56) and low consumption of green leafy vegetables (OR = 1.91, 95% CI = 1.12-3.24). Forty-one (29.1%) of the prestroke depression sub-sample developed PSD. However, prestroke depression was not significantly associated with PSD. Conclusion: The findings should energize before-the-stroke identification and prioritization of limited treatment resources in LMICs to persons with depression who have multiple, additional, risks of stroke.